1141. Microbial Assessment of Healthcare-Associated Pathogens on Various Environmental Sites in Patient Rooms After Terminal Room Disinfection. (26th November 2018) - Kanamori, Hajime; Rutala, William; Gergen, Maria; Sickbert-Bennett, Emily; Anderson, Deverick J; Sexton, Daniel; Weber, David
Abstract: Background: Hospital room environmental surfaces can be contaminated with healthcare-associated pathogens even if terminal room cleaning/disinfection is implemented. We examined the microbiological burden on hospital room environmental sites after standard or enhanced terminal room disinfection. Methods: Microbial data from the Benefits of Enhanced Terminal Room Disinfection Study were utilized. All patient rooms were randomly assigned to standard disinfection (Quaternary ammonium [Quat]) or an enhanced disinfection (Quat/ultraviolet light [UV-C], Bleach, or Bleach/UV-C). Microbiological samples were obtained using Rodac plates (25 cm 2 /plate) from 8 of 10 hospital room sites, including bed rail, over-bed table, supply/medicine cart, chair, side counter, linen hamper lid, sink, toilet seat, shower floor, and bathroom floor. The number of colony forming units (CFU) of four target epidemiologically important pathogens (EIP), including multidrug-resistant Acinetobacter, Clostridium difficile, methicillin-resistant Staphylococcus aureus, and vancomycin-resistant enterococci, was counted. A total of 3, 680 samples from 736 environmental sites in all 92 patient rooms (21 standard rooms and 71 enhanced rooms) were analyzed. Results: Overall, the frequency of all environmental sites positive for EIP was 11% (84/736) in all rooms, 21% (36/168) in standard rooms, and 8% (48/568) in enhanced rooms ( P < 0.001) (Figure 1). Environmental sites, other than the toilet seat, in standard rooms were likely to be more frequently contaminated with EIP than in enhanced rooms ( P = 0.013 for overbed table, P = 0.010 for bed rail, and P > 0.05 for other sites each). Mean CFU of EIP per room was 19.2 in all rooms, 60.8 in standard rooms, and 6.9 in enhanced rooms ( P = 0.006) (Figure 2). All sites in standard rooms tended to have higher mean counts than in enhanced rooms ( P = 0.001 for overbed table, P = 0.001 for bed rail, P = 0.012 for side counter, and P > 0.05 for other sites each). Conclusion: Our results demonstrate that an enhanced terminal room disinfection reduced microbial burden of healthcare-associated pathogens on environmental sites better than standard room disinfection. Environmental hygiene of touchable surfaces after terminal room cleaning using Quat needs to be improved. Disclosures: W. Rutala, PDI: Consultant and Speaker's Bureau, Consulting fee and Speaker honorarium. D. Weber, PDI: Consultant, Consulting fee.